Hubungan Kompetensi Profesional Guru Biologi dengan Hasil Belajar Siswa di SMAS GKLB Luwuk - Marjuno, Siti Aisyah; Kenta, Abdul Muin; Anggo, Sulasmi; Liise, Hamli Jein's Steven (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2024)
Teacher professional competence refers to the abilities, knowledge and skills possessed by teachers in carrying out the learning process. This research aims to determine the relationship between biology teachers' professional competence and student learning outcomes at SMAS GKLB Luwuk. This research uses a quantitative approach with descriptive methods. Data was collected through a questionnaire filled in by 30 students as respondents. The results of the research show that there is a significant positive relationship between the professional competence of biology teachers and student learning outcomes. The higher the teacher's professional competence, the better the student learning outcomes as reflected in their academic scores. These findings emphasize the importance of developing teacher professional competence as a key factor in improving the quality of education and student learning outcomes in schools. Recommendations from this research include the need for ongoing training and development programs for biology teachers to improve their skills and knowledge.